Penatalaksanaan Fisioterapi pada Kondisi Bell’s Palsy Sinistra dengan Modalitas Infrared, Electrical Stimulation Arus Faradik dan Terapi Latihan di RSUD Bendan Kota Pekalongan - Anggraeni Puji Safitri; Andung Maheswara Rakasiwi (Pusat Riset dan Inovasi Nasional, 2022)
Bell's palsy is a neurological disorder and disorder of the cranial nerve VII (facial nerve) in the temporal bone area that causes weakness or paralysis of the facial muscles around the stylomastoid foramen. The cause is not known to be vascular ischemia, viral disease (Herpes simplex, Herpes zoster), autoimmune disease, or a combination of these factors. The purpose of this study was to determine the effect of Physiotherapy Management in Bell's Palsy with Infra Red, Electrical Stimulation of Faradic Current and Exercise Therapy as modalities. The study was conducted at Bendan Hospital, Pekalongan City with descriptive analytic method in patients with Bell's Palsy condition. Methods of collecting research data using autoanamnesis and physical examination. The research instrument consisted of examining pain using the Visual Analogue Scale, muscle spasm with palpation, muscle strength using manual muscle testing, and functional activity using the Ugo Fisch scale. After therapy 1 to therapy 4 there was a decrease in pain from T1 = tenderness 4 to T4= tenderness 0. Increased facial muscle strength T1 = m. orbicularis oculi 3 to T4 = m.orbicularis oculi 5. Decreased muscle spasm T1 = m. frontalis 1, m. corrugator supercilli 1, m. zygomaticum 1, m. orbicularis oris 1, m. mentality 1 to T4 = m. frontalis 0, m. corrugator supercilli 0, m. zygomaticum 0, m. orbicularis oris 0, m. mentalis 0. The conclusion is Infra Red, Electrical Stimulation of faradic currents and Exercise Therapy can reduce pain, decrease muscle spasm and increase muscle strength on Bell’s Palsy Sinistra.